Marketing and institutional factors in the voluntary adoption of corporate social responsibility reporting: The case of global reporting initiative - Bicho, Marta (2010)
Corporate Social Responsibility (CSR) has increased substantially in the last decades. Various studies have identified that the greater importance of CSR is parallel to the rise of public information about CSR activities and also to the stakeholders’ demands. In fact, companies are engaging in reporting their CSR activities. This research is interested in what makes companies engage into voluntary reporting? It focus our research on the world's most widespread framework of CSR reporting - the Global Reporting Initiative (GRI). To the bet of our knowledge, this is the first study to address what drives companies into the adoption of GRI framework. We purposed that institutional pressure together with marketing factors, namely as brand equity, media visibility and publicity could be relevant determinants of GRI adoption. Data on 600 global companies was gathered from public data sources to construct the variables for our model. We tested our model by fitting a logistic regression with the dependent variable of GRI adoption. The findings suggest that institutional pressures, in particular imitative behavior and the transparency culture of the home country of companies persuade companies to be aware of the importance of reporting their CSR activities and consequently adopt the GRI practices. Also, CSR communications of CSR activities and public relations play an important role in the decision-making of GRI voluntary adoption.